Abnormal beta and gamma frequency neural oscillations mediate auditory sensory gating deficit in schizophrenia. (May 2020) - Nguyen, Ann T.; Hetrick, William P.; O'Donnell, Brian F.; Brenner, Colleen A.
Abstract: Background: Sensory gating is a process in which the brain's response to irrelevant and repetitive stimuli is inhibited. The sensory gating deficit in schizophrenia (SZ) is typically measured by the ratio or difference score of the P50 event-related potential (ERP) amplitudes in response to a paired click paradigm. While the P50 gating effect has usually been measured in relation to the peak amplitude of the S1 and S2 P50 ERPs, there is increasing evidence that inhibitory processes may be reflected by evoked or induced oscillatory activity during the inter-click interval in the beta (20–30 Hz) and gamma (30–50 Hz) frequency bands. We therefore examined the relationship between frequency specific activity in the inter-click interval with gating effects in the time and frequency domains. Method: Paired-auditory stimuli were presented to 131 participants with schizophrenia and 196 healthy controls (HC). P50 ERP amplitudes to S1 and S2as well as averaged- and single-trial beta (20–30 Hz) and gamma (30–50 Hz) frequency power during the inter-click interval were measured from the CZ electrode site. Results: In the time domain, P50 gating deficits were apparent in both ratio and difference scores. This effect was mainly due to smaller S1 amplitudes in the patient group. SZ patients exhibited less evoked beta and gamma power, particularly at the 0–100 ms time point, in response to S1. Early (0–100 ms) evoked beta and gamma responses were critical in determining the S1 amplitude and extent of P50 gating across the delay interval for both HC and SZ. Conclusion: Our findings support a disruption in initial sensory registration in those with SZ, and do not support an active mechanism throughout the delay interval. The degree of response to S1 and early beta and gamma frequency oscillations in the delay interval provides information about the mechanisms supporting auditory sensory gating, and may provide a framework for studying the mechanisms that support sensory inhibition.